The localization and functional analysis - Watanabe, K (2011)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is the most recently characterized Ca2+ mobilizing second messenger, joining inositol 1,4,5-trisphosphate (IP3) and cyclic ADP-ribose (cADPR). Previous pharmacological and biochemical studies have suggested that NAADP targets acidic Ca2+ stores rather than the ER, which releases Ca2+ in response to IP3 or cADPR. Although NAADP receptors are proposed to be distinct from those for IP3 and cADPR, the molecular identity of NAADP receptors has remained elusive. This study focuses on establishing whether two-pore channels (TPCs), a family of intracellular Ca2+-release channels, function as NAADP receptors. In this thesis, TPC proteins have been investigated as potential NAADP receptors in the sea urchin, Strongylocentrotus purpuratus, whose genome encodes three potential TPC proteins, namely SpTPC1, SpTPC2 and SpTPC3, and in the social amoeba, Dictyostelium discoideum, which encodes only one TPC2 (DdTPC2). These channels were analyzed in multiple model systems namely the sea urchin egg, human cell lines (HEK cells and HeLa cells), an insect cell line (sf9) and Dictyostelium. Analytical approaches including the generation of anti-TPC antibodies, localization studies, ligand binding assays and Ca2+ release studies were employed. SpTPC1 and SpTPC2 were predominantly localized to the ER and the lysosome, respectively. Endogenous sea urchin protein immunoprecipitated with anti-SpTPC3 antibody showed enhanced NAADP binding. However, no correlation between NAADP binding and expression levels of TPCs in HEK cells or Sf9 cells was detectable. In Dictyostelium, TPC2 was localized to the contractile vacuole and the ER, whereas DdTPC2 localized to the lysosome and Golgi apparatus when expressed in HeLa cells. Protein expression of DdTPC2 is regulated developmentally, reaching a peak in the late stages of development. A tpc2 null strain exhibited abnormal post-aggregative development, consistent with a role for DdTPC2 at later stages of development. No high affinity NAADP binding sites or NAADP-induced Ca2+ release were detected in Dictyostelium membranes isolated either at the early or late development stages in these studies. However, NAADP-induced Ca2+ release from vesicle fractions prepared from vegetatively growing cells was observed. On the other hand, arachidonic acid (AA) induced Ca2+ release from vesicles prepared from growing cells and from cells developed for 4 hours or 20 hours. AA-induced Ca2+ release was altered in tpc2 null cells. In sea urchin egg homogenate, AA also elicited Ca2+ release with an EC50 value of approximately 8 μM. Low concentrations of AA effectively inhibited NAADP-induced Ca2+ release. It was not possible to produce evidence of TPCs being NAADP-sensitive Ca2+ channels in the systems investigated. In Dictyostelium, TPC2 does not appear to be responsible for NAADP-induce Ca2+ release. However, TPC2 may play a role in AA-induced Ca2+ release.